2001
DOI: 10.2337/diabetes.50.5.1149
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Antidiabetic Properties of Conjugated Linoleic Acid

Abstract: Conjugated linoleic acid (CLA) isomers have a number of beneficial health effects, as shown in biomedical studies with animal models. Previously, we reported that a mixture of CLA isomers improved glucose tolerance in ZDF rats and activated peroxisome proliferatoractivated receptor (PPAR)-␥ response elements in vitro. Here, our aim was to elucidate the effect(s) of specific CLA isomers on whole-body glucose tolerance, insulin action in skeletal muscle, and expression of genes important in glucose and lipid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
214
4
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(249 citation statements)
references
References 44 publications
(51 reference statements)
21
214
4
6
Order By: Relevance
“…8,9 In the present investigation, some improvements in the deranged metabolic regulation of the female obese Zucker rat were elicited at a substantially lower dose of CLA (0.3 mg/kg). For example, the low-dose CLA treatment caused decreases in fasting plasma glucose and FFAs (Table 1), improved whole-body glucose tolerance and insulin sensitivity (Fig 2), and increased insulin-mediated glucose transport activity in fast-glycolytic muscle (Fig 3).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…8,9 In the present investigation, some improvements in the deranged metabolic regulation of the female obese Zucker rat were elicited at a substantially lower dose of CLA (0.3 mg/kg). For example, the low-dose CLA treatment caused decreases in fasting plasma glucose and FFAs (Table 1), improved whole-body glucose tolerance and insulin sensitivity (Fig 2), and increased insulin-mediated glucose transport activity in fast-glycolytic muscle (Fig 3).…”
Section: Discussionmentioning
confidence: 58%
“…However, recent studies by Riserus et al 39,40 in abdominally obese human males have indicated that treatment with CLA (specifically the trans-10, cis-12 isomer) actually worsened slightly insulin resistance (19%) and glycemia (4%) and was associated with an increase in oxidative stress (based on plasma isoprostanes). Based on these limited clinical findings, and in the context of the positive results from the present study and previous investigations, 8,9 it is clear that subjects in human clinical trials of CLA must be selected very carefully to ensure that they will be appropriate candidates for CLA treatment of obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…O aumento da termogênese induzida pelo CLA tem sido discutido também como responsável pela redução da gordura corporal, já demonstrada em camundongos AKR/J, Std ddY e C57BL/6J e ratos ZDF 88,[121][122][123] . Segundo Tsuboyama-Kasaoka et al 88 e Ryder et al 122 , o aumento do gasto energé-tico observado nesses animais é resultante do aumento da expressão de genes que codificam as proteínas desacopladoras (UCP), especialmente a UCP-2, visto que os autores encontraram aumento dos níveis tanto do mRNA quanto da proteína no tecido adiposo branco, músculo esquelético e fígado dos animais.…”
Section: Cla Metabolismo De Glicose E Lipídeos E Composição Corporalunclassified